Composite endpoints in trials of type‐2 diabetes. Issue 6 (8th November 2013) - Einarson, T. R.; Garg, M.; Kaur, V.; Hemels, M. E. H.
<x xml:space="preserve">Abstract</x> Composite endpoints (CEPs) are being used more frequently as outcomes for trials of drugs in type‐2 diabetes. We reviewed the literature to determine how CEPs have been used to date in trials of drugs for type‐2 diabetes. A systematic search was undertaken on Medline, Embase and Cochrane databases and Clinicaltrials.gov for randomized controlled trials of currently marketed agents including SGLT‐2 inhibitors (dapagliflozin), GLP‐1 agonists (exenatide, liraglutide) and DPP‐4 inhibitors (linagliptin, saxagliptin, sitagliptin and vildagliptin). CEPs used were identified as well as numbers and percentages of patients achieving each. Thirty‐six studies were identified that reported results on ≥1 CEP; 15 different CEPs were reported (7 with 2 components, 8 with 3 components). All CEPs addressed goals recommended by the American Diabetes Association (ADA). All included HbA1c<7%; other endpoints measured weight, blood pressure and hypoglycaemic events. Results were obtained for CEPs from 6 months to 2 years. Rates of achieving CEPs decreased with increasing numbers of components and outcomes assessed. CEPs are becoming used as indicators of clinical outcomes in type‐2 diabetes trials, but are still not common. More research is required to identify optimal CEPs. Standardization of outcomes and their reporting is needed.